Prescription patterns of pancreatic enzyme replacement therapy for patients with pancreatic cancer in the United States. Issue 10 (October 2022) - Jain, Tejeshwar; Sharma, Prateek; Giri, Bhuwan; Iyer, Srikanth; Sethi, Vrishketan; Bava, Ejas P.; Vaish, Utpreksha; Sahay, Preeti; Datta, Jashodeep; Reddy, Sushanth; Bart Rose, John; Khan, Anam; et al.
Abstract: Background: Exocrine pancreatic insufficiency (EPI) is frequently seen in patients with pancreatic cancer (PDAC) and is thought to contribute to nutritional complications. While EPI can be pharmacologically temporized with pancreatic enzyme replacement therapy (PERT), there is lack of clear evidence informing its use in PDAC. Here we aim to survey pancreatic surgeons regarding their utilization of PERT in the management of EPI for PDAC. Methods: An online survey was distributed to the members of The Americas Hepato-Pancreato-Biliary Association (AHPBA) and The Pancreas Club. Results: 86.5% (180/208) of surgeons prescribe PERT for at least some resectable/borderline resectable PDAC cases. Only a minority of surgeons order investigations to confirm EPI before starting PERT (28.1%) or test for adequacy of therapy (28.3%). Few surgeons believe that PERT has an effect on overall survival (19.7%) or disease-free survival (6.25%) in PDAC. Conclusion: PERT is widely prescribed in patients with resectable/borderline resectable PDAC, but investigations establishing EPI and assessing PERT adequacy are underutilized. A substantial proportion of surgeons are unclear as to the effect of PERT on survival outcomes in PDAC. These data call for prospective studies to establish guidelines for optimal use of PERT and its effects on survival outcomes in PDAC.